2019
DOI: 10.1111/iji.12446
|View full text |Cite
|
Sign up to set email alerts
|

TLR‐2, TLR‐4 and MyD88 genes expression in renal transplant acute and chronic rejections

Abstract: Background Graft rejection due to alloreactivity is still the main obstacle to successful renal transplantation. Toll‐like receptors (TLRs), which are significantly involved in initiating inflammation, triggering innate immunity, occurrence of ischaemia reperfusion injury (IRI) and subsequent deterioration of allograft function, are of interest in molecular diagnosis of graft rejection. Methods In present research, we have evaluated the mRNA expressions of TLR‐4, TLR‐2 and myeloid differentiation primary respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Increased messenger RNA expression of TLR2 in the cardiac allograft is associated with increased risk of cardiac allograft rejection in humans ( 141 ). This is in line with earlier studies showing similar findings in kidney transplantation ( 143 , 144 ). A recent study using TLR2-deficient mice on the other hand showed poor graft survival time, due to increased immune cell infiltration and enhanced pro-inflammatory Th17 cell responses ( 148 ).…”
Section: Pattern Recognition Receptors Related To Myocardial Ischemiasupporting
confidence: 94%
See 1 more Smart Citation
“…Increased messenger RNA expression of TLR2 in the cardiac allograft is associated with increased risk of cardiac allograft rejection in humans ( 141 ). This is in line with earlier studies showing similar findings in kidney transplantation ( 143 , 144 ). A recent study using TLR2-deficient mice on the other hand showed poor graft survival time, due to increased immune cell infiltration and enhanced pro-inflammatory Th17 cell responses ( 148 ).…”
Section: Pattern Recognition Receptors Related To Myocardial Ischemiasupporting
confidence: 94%
“…There is strong evidence that TLR4 contributes to IRI in both MI (138)(139)(140) and HTx (137,141). The role of TLR4 in transplantation has also been confirmed for other solid organ transplants (142)(143)(144)(145). Given these observations, TLR4 inhibition may have beneficial effects in limiting IRI.…”
Section: Tlr4mentioning
confidence: 89%
“…Our group characterized the molecular signature of PBMCs and CD4+ T lymphocytes isolated from patients with chronic antibody-mediated rejection, demonstrating the specific activation of interferon alpha signaling [8]. Sharbafi et al reported that increased gene expression of toll-like receptor 4 (TLR4) in PBMCs could be suggestive of cell-mediated rejections [9]. Danger et al described that miR-142-5p in circulating immune cells might represent a useful as a biomarker in antibody-mediated rejection [10].…”
Section: Introductionmentioning
confidence: 94%
“…Glomerular TLR4 expression was also associated with the severity of renal injury [37]. MyD88 gene upregulation in renal tissue and increased levels of TLR4 mRNA in peripheral blood mononuclear cells (PBMCs) have been reported as being suggestive of cell-mediated rejection [38] or graft dysfunction in kidney transplantation [39]. TLR2 and TLR4 have been identified as proinflammatory and fibrotic receptors in peritoneal dialysis (PD), after microbial-and sterile inflammationinduced responses [40].…”
Section: Toll-like Receptor Expression In Human Kidney Diseasesmentioning
confidence: 99%